Analisis Kinerja Keuangan Setelah Implementasi Pola Pengelolaan Keuangan Badan Layanan Umum Daerah (PPK-BLUD) - Ari Ardiansyah (OPTIMAL Jurnal Ekonomi dan Manajemen, 2023)
The purpose of this study is to understand the financial activities of the Melata Health Center after the implementation of the BLUD (2020-2022). The background of the problem is that people's welfare needs to be improved through improving the performance of government organizations, for example in the establishment of BLU/D. Health Center is one example of community organization. The organization places more emphasis on providing services to society than making a profit. Research is one type of research. Data obtained through the creation of documentation. Techniques for analyzing desktop quantitative information for the purpose of determining employment rates based on currency exchange rates. The research findings show that the financial activities of the Melata Health Center in 2020, 2021 and 2022 will be carried out using various indicators of the PNBP ratio on operational costs, inventory turnover, equity returns, fixed asset returns, fixed asset turnover, receivables collection period, current ratio, and cash ratio based on Director General of Treasury Regulation No. PER-36/PB/2016.